Digit Recognition and Classification from Digital Display Without Network Connection - Paweł KACZMAREK; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2021)
The paper describes an approach to recognizing numbers from digital displays using convolutional neural networks and computer vision. The proposed approach is to use the solution on a mobile device under the control of the Android operating system without using the Internet or mobile data. The aim of the research is to create an autonomous application that will flawlessly recognize the digits on the display, so that it can make specific decisions based on the data, including saving lives or supporting the Internet of Things.
Keywords: Digit recognition; CNN classification; web neural network.